Ordnung der Verunordnung transterritorialer Stadtlandschaften: Die Nürnberger Gartenvorstadt Werderau im globalen Zeitalter - Berndt, Christian; Boeckler, Marc (ERDKUNDE, 2005)
Approaching struggles for political representation through a perspective of methodological cosmopolitanism, the paper makes sense of recent developments evolving around a territorialized urban neighbourhood in Nuremberg, Northern Bavaria. Founded at the beginning of the 20th century by a mechanical engineering company as a garden suburb restricted to employees, the neighbourhood enjoyed relative protection from globalizing frictions and struggles until the world-in-motion suddenly penetrated the community a few years ago. Following a brief introduction, section two charts the production of the bounded settlement as a site of alternate social ordering at a time of hyper-industrialisation and its imaginary role as territorial heterotopia, symbolising order in a seemingly chaotic urban world. Turning to the owner's decision to sell the neighbourhood in 1998 in section three, we argue that long-term inhabitants discursively frame the events following the decision as transterritorial pollution of their bounded community, reflected in the commodification of their neighbourhood and in an invasion of non-German home-owners. After discussing how longer-term residents attempt to re-stabilise their identities by taking up a xenophobic discourse (section four), we conclude by criticising policy-makers for responding solely in a territorial logic and for one-sidedly taking up the discourse advanced by long-term residents. Instead we make a utopian plea for transterritorial politics in the multiplied city, advancing a vision of the city as both cosmos and polis, a transcultural crossroads where movement and distanciation are the norm.